2012
DOI: 10.22605/rrh2193
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating medical withdrawal from opiates in rural Ontario

Abstract: The abuse of oxycodone in Northwestern Ontario, Canada, has escalated at alarming rates raising concerns that opiate use has reached epidemic proportions, particularly among the First Nations communities. The authors were involved in establishing Ontario's first rural inpatient medical withdrawal unit to serve patients seeking abstinence. Issues: The development of the medical withdrawal support services (MWSS) required creative and adaptive strategies to respond to the geographical, cultural and institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…This association with individuals' location of residence is important because it shows the regional variation in OAT retention within various cascades. Interestingly, despite the wellknown barriers to accessing addiction and related services in rural areas due to limited access to providers and long distances to travel, 24,52,53 our ndings are also re ected in a previous Ontario based-study which found that OAT patients in Northern regions (both urban and rural) were more likely to be retained in methadone maintenance therapy compared to the Southern regions. 54 Notably, the study by Eibl et al, used administrative data from 2003-2012 in contrast to our study timeline which is 2014-2020, which strengthens the evidence-base relating to geography and OAT.…”
Section: Discussionsupporting
confidence: 69%
“…This association with individuals' location of residence is important because it shows the regional variation in OAT retention within various cascades. Interestingly, despite the wellknown barriers to accessing addiction and related services in rural areas due to limited access to providers and long distances to travel, 24,52,53 our ndings are also re ected in a previous Ontario based-study which found that OAT patients in Northern regions (both urban and rural) were more likely to be retained in methadone maintenance therapy compared to the Southern regions. 54 Notably, the study by Eibl et al, used administrative data from 2003-2012 in contrast to our study timeline which is 2014-2020, which strengthens the evidence-base relating to geography and OAT.…”
Section: Discussionsupporting
confidence: 69%
“…One additional source was retrieved via a scan of article references. A total of 27 sources were identified that met inclusion criteria, including 12 qualitative [19][20][21][22][23][24][25][26][27][28][29][30], 6 quantitative [31][32][33][34][35][36], 6 mixed-methods [37][38][39][40][41][42], and 3 reviews [43][44][45]. Most of the articles examined perspectives or outcomes of client or community members on substance use programmes wholly or partially aimed at opioid use [19, 24-26, 31-37, 40, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Contextual factors contributing to opioid dependence described in the articles often included discussions of a complex interaction of social conditions in the sampled community. The social determinants of health outlined included poverty [22,40,42], unemployment [22,42], poor health [22], low education levels [22,42], low economic development [22], incarceration [39], singlemotherhood [40], domestic violence [40], racism [42], residential school experiences [22], legacies of colonialism on territorial and cultural dislocation [27], and emotional responses to colonization including grief [39], and emotional trauma and loneliness through the loss of loved ones and personal identity [43]. The social determinants of health in Indigenous contexts have been outlined in the literature; for the purpose of this realist review, the context extraction focused on program descriptions (Table 1).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that medical clinics not limit patient engagement and success to factors within the patientprovider dyad, as this will overlook the importance of community support, culture, social restoration, and belonging. Cultural awareness and creative and adaptive strategies are needed to respond to the geographical, cultural, and institutional circumstances that typify rural and remote communities [65,66]. Although evaluation of OAT programs is typically centred on the patient-provider dyad, the Sioux Lookout OAT program is community-wide and focused on welcoming substance-dependent patients back to their families and previous roles.…”
Section: Discussionmentioning
confidence: 99%